Broadcasting Adaptation in the Streaming Era: Industrial Transformation in the Digital Revolution - Ibrahim, Riza Andrian; Hidayana, Rizki Apriva; Saefullah, Rifki (International Journal of Linguistics, Communication, and Broadcasting, 2024)
In an era of ever-evolving streaming revolution, the broadcasting industry is facing major transformation to adapt and survive. Broadcasters need to adopt new strategies in business models and monetization, such as combining subscriptions, individual purchases, data-driven advertising, as well as partnerships with large streaming platforms through a hybrid approach. Investing in producing unique and engaging original content is also critical to differentiate yourself from competitors and cater to diverse audience preferences by exploring new genres and formats. In terms of technological infrastructure, increasing network capacity, servers and hardware are needed to support high-quality streaming, as well as paying attention to security and redundancy to ensure continuity of operations. Moreover, data measurement and analytics are key by developing new, relevant metrics to measure content performance, understand consumer behavior and preferences, and optimize monetization strategies. Leveraging data also allows for better personalization of content according to viewers' individual interests. By adopting a comprehensive approach in all these aspects, broadcasters can adapt effectively and achieve long-term success in an increasingly competitive streaming era.